The experience of the emergency psychologist during the Covid-19 pandemic: A qualitative research - Rossi, Sandra; Carbone , Roberta; Pedrelli , Enrica; Artioli, Giovanna; Sozzi, Anna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2021)
Abstract. Background and aim of the work: the new coronavirus pandemic COVID-19 has had a strong psy- chological impact on the world population. Volunteer psychologists, and psychologists that work in the emer- gencies have also been exposed to the consequences of the impact of the pandemic. The purpose of this study was to explore the experiences of the psychologist during the Covid-19 emergency intervention. Methods: an exploratory study, following a qualitative design using Focus Group method was adopted. A total of 24 psychologists was recruited from volunteers of the “Pronto Pșy - Covid-19” service, organized by the Ital- ian Society of Emergency Psychology Social Support, Emilia Romagna. Focus Group Discussions (FGDs) was held about: their experiences during the online psychological support; needs detected by users; training needs that emerged during the intervention and professional skills applied. Results: five themes were identi- fied: psychological distress of rescuers; online emergency setting; support of colleagues and gratitude as stress management strategies; need of skill and tools in pandemic emergency intervention; integrated psychological intervention. Discussion: the stress reaction of the emergency psychologists was due in particular to the type of emergency and lack of standardized approach. The group meetings represented an important resource to face traumatic stress. Conclusions: this study showed the role the need for specific tools for pandemic intervention to protect the well-being of the professional from impact of stress. Further research is needed.(www.actabiomedica.it)